Design and theoretical performance prediction of hydrogen peroxide hybrid thruster - Muhalim, Noor Muhammad Feizal (2009)
A design procedure to realize a hybrid rocket engine that uses hydrogen peroxide as the oxidizer and a solid polymer as the fuel is presented. In the design procedure, the products of decomposition and of combustion at different stations are calculated by linking a standard complex chemical-equilibrium program of NASA. For the designed basic-configuration, applying the mass conservation principle, theoretical performance results are presented with propellant-tank pressure and grain port length as parameters.